The role of augmented reality in halal beauty shopping experience - Mardhiyah, Dien; Futuwwah, Ali Imaduddin; Susilowati, Fitriah Dwi; Osman, Syuhaily; Gozali, Nidia Artanti; Putri, Nadia Ramadhani Nugroho (al-Uqud : Journal of Islamic Economics, 2025)
Augmented Reality (AR) is rapidly evolving and being integrated into various business sectors, including the halal cosmetics industry. Additionally, AR helps prevent contamination from non-halal ingredients and reduces the spread of diseases associated with shared testers. Despite these advantages, consumer adoption of AR in online cosmetic selection remains low. Many shoppers still cannot use AR, despite its vividness, interactivity, and customizable features, which can significantly enhance product exploration and foster a positive perception of the technology. This study investigates the key factors influencing consumers' intentions to use AR when purchasing halal cosmetics, employing the SOR theory as a framework. Through a quantitative approach and SEM-PLS analysis, the findings reveal that AR attributes play a crucial role in creating a more immersive and compelling halal shopping experience. These insights offer valuable guidance for businesses seeking to develop AR-driven marketing strategies—an approach that remains underutilized in the halal cosmetics industry. By leveraging AR technology, companies can bridge the gap between online and offline shopping, enhance consumer confidence, and drive greater engagement in the halal beauty market.